Comparison of Chloroaluminate Melts for Aluminum Graphite Dual‐Ion Battery Application. Issue 2 (23rd November 2020) - Elia, Giuseppe Antonio; Hoeppner, Katrin; Hahn, Robert
Abstract: Herein, we report a comparison of aluminum graphite dual‐ion cells (AGDICs) electrochemical characteristics employing the conventional 1‐ethyl‐3‐methylimidazolium chloride:aluminum trichloride (EMIMCl : AlCl3 ) electrolyte and two popular deep eutectic solvents (DESs), namely urea : AlCl3 and acetamide:AlCl3 . The three electrolytes′ characteristics have been evaluated in terms of Al‐stripping deposition capability and cycling behavior in AGDICs. The results evidence the EMIMCl : AlCl3 ′s Al‐stripping deposition and rate capability in AGDICs superior characteristics addressed to the lower viscosity and higher conductivity with respect to the urea : AlCl3 and acetamide:AlCl3 . On the other hand, the urea : AlCl3 guarantees a much higher columbic efficiency in AGDICs, thanks to the superior electrochemical window stability. Abstract : Let the best electrolyte win ! A comparison of aluminum graphite dual‐ion cells (AGDICs) electrochemical characteristics employing the conventional 1‐ethyl‐3‐methylimidazolium chloride:aluminum trichloride (EMIMCl : AlCl3 ) electrolyte and two popular deep eutectic solvents (DESs), namely urea : AlCl3 and acetamide:AlCl3, is shown here.